The rationale of progress - White, Charles Bernard (My University, 1899)
Introduction: “Life is what we make it.” Says the proverb, and perhaps more science never got into fewer words. Life, the fife of any organism, plant, animal, or the life of the organism, society, is simply what that organism makes of itself. It is the progressive realization of an ideal, the bodying forth of thought in a mode of manifestation which constitutes that form of life. Life is one, with many forms. Whatever may be true of other forms, the organism we call “man” is conscious of at least a part of the process which constitutes his being. He knows some of his relations to other forms, may compare other forms together, and with himself, and do reason from the parts toward the whole. He gains some knowledge of the plan of the whole by tracing the plan of the parts. When man has reached the stage of self-knowledge, he becomes self-directive, with power to choose. When he forms some conception of the ideal of which he is the expression, he begins to be responsible for that expression.
Citation: White, Charles Bernard. The rationale of progress. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Conscious Movement; Action; Unconscious Movement; Theses; Manuscripts (documents)